Immunogenic cell death as driver of autoimmunity in granulomatosis with polyangiitis - Brieske, Christoph; Lamprecht, Peter; Kerstein-Staehle, Anja (Frontiers in Immunology, 2022)
Cell death and dysregulated clearance of dead cells play essential roles in the induction of chronic inflammatory processes and autoimmune diseases. Granulomatosis with polyangiitis (GPA), a neutrophil-driven autoimmune disorder, is characterized by necrotizing inflammation predominantly of the respiratory tract and an anti-neutrophil cytoplasmic autoantibody (ANCA)-associated systemic necrotizing vasculitis. Defective regulation of neutrophil homeostasis and cell death mechanisms have been demonstrated in GPA. Disturbed efferocytosis (i.e., phagocytosis of apoptotic neutrophils by macrophages) as well as cell death-related release of damage-associated molecular patterns (DAMP) such as high mobility group box 1 (HMGB1) contribute to chronic non-resolving inflammation in GPA. DAMP have been shown to induce innate as well as adaptive cellular responses thereby creating a prerequisite for the development of pathogenic autoimmunity. In this review, we discuss factors contributing to as well as the impact of regulated cell death (RCD) accompanied by DAMP-release as early drivers of the granulomatous tissue inflammation and autoimmune responses in GPA.